Appendix 1A: Agricultural transformation in Ethiopia: What do we know? - Berhane, Guush; Bachewe, Fantu Nisrane; Minten, Bart (Alliance for a Green Revolution in Africa, 2018)
Ethiopia has achieved substantial progress in triggering and generating sustained agricultural growth for more than a decade. At the center of these favorable changes is an important political commitment that early on recognized the need to put agriculture at the center of its development agenda. This fundamentally shaped Ethiopia’s approach to addressing its age-old problems of structural bottlenecks for development. As such, the government envisioned overall development around an agriculture-first and then industrialize approach with a series of strategies put in place to execute this grand vision. As a result, Ethiopia and its development partners have invested heavily in putting in place not only development programs and projects but also the critical institutional and governance structures to implement them. This required instituting government structures, at times at the cost being too bureaucratic, and building new government and semi-government organizations tasked to achieve agricultural transformation.